Ouest-France : un média plateforme ? Politique de diversification, jeu de placement de l’information et zonage des pratiques en ligne - Sandra MELLOT; Anaïs THEVIOT (Tic & Société)
In the face of increasing economic constraints, most major local and national media adopt positions that display symptoms of the “platformisation” of production. We examine the case of the leading French regional newspaper, Ouest-France, to question the platform future of media. This indepth case study is based on analysis of the design of its various sites, as well as thirty interviews with local daily newspaper journalists on the reconfiguration of their profession. This article shows that the Ouest-France group inscribes its strategy in a platform logic by taking advantage of the different strategic and economic models of the digital world to spread its presence and to adapt the practice of journalism to the new temporalities and multimodalities expected of the Web. This fragmentation of communication contrasts with the confinement of practices in unrelated editorial spaces, however.